Tart Cherry Juice in Athletes: A Literature Review and Commentary. Issue 4 (July 2017) - Vitale, Kenneth C.; Hueglin, Shawn; Broad, Elizabeth
Abstract : Tart cherry (TC) juice has many antioxidant and anti-inflammatory polyphenol compounds. TC lessens pain and accelerates strength recovery after exercise and decreases blood markers of inflammation/oxidative stress. These improvements occur in both strength and endurance exercise. TC supplementation may not be optimal during the adaptation/build stage of training. However, excessive inflammatory/oxidative stress during single-day intense training/competition or multiday tournaments may delay return to peak form. In this stage, where recovery (not adaptation) is the priority, TC may be beneficial. Timing and dosage vary widely, but most studies use 8 to 12 oz (1 oz if concentrate form) twice a day, 4- to 5-d loading phase before the event, and 2 to 3 d after to promote recovery. Therefore, for an athlete who has already peaked in training and looking to improve recovery and faster return to competition, TC may be beneficial. Abstract : Summary Statement: Tart cherry juice in athletes may reduce pain, inflammation/oxidative stress, and promote faster recovery to baseline. Preliminary studies suggest improved performance.